Epileptic seizures in a descendant of Dom Pedro I Crises epilépticas em uma descendente de Dom Pedro I - Marleide da Mota Gomes; Heber de Souza Maia Filho (Arquivos de Neuro-Psiquiatria, 2010)
Intrauterine seizure is a rare event. Genetic predisposition and trauma are possible risk factors. OBJECTIVE: To review and comment on the historical description of intrauterine events of a bastard daughter of Dom Pedro I (Maria Isabel Alcântara Brasileira - 1830-1896). METHOD: Review of historical facts about the health of Dom Pedro I's daughter according to primary and secondary historical data. RESULTS: According to historical accounts, Dom Pedro I's daughter suffered trauma during the intrauterine period that provoked intrauterine seizures. At the age of eight years, she developed self-limited and benign generalized epilepsy. Like her father, she had mood problems and also learning difficulties. CONCLUSION: Dona Maria Isabel's own report does not shown sufficient evidence to support the diagnosis of post-traumatic intrauterine seizures. Nevertheless, her family history suggests a genetic basis for her epilepsy. A convulsão intra-uterina é evento raro, sendo possíveis fatores de risco a genética e o traumatismo. OBJETIVO: Rever e comentar a descrição histórica de eventos intra-uterinas de uma filha bastarda de D. Pedro I (Maria Isabel Alcântara Brasileira - 1830-1896). MÉTODO: Revisão dos fatos históricos sobre a saúde da filha do D. Pedro I, de acordo com dados históricos primários e secundários. RESULTADOS: A filha de Dom Pedro I, de acordo com relatos históricos teria sofrido um traumatismo durante o período intra-uterino, o que provocou convulsões intra-uterinas. Na idade de oito anos a menina desenvolveu uma epilepsia generalizada limitada e benigna. Como seu pai, teve problemas do humor e, também, dificuldades de aprendizagem. CONCLUSÃO: O relato de Dona Maria Isabel não gera prova suficiente para sustentar o diagnóstico de convulsões intra-uterinas de origem traumática. Não obstante, seus antecedentes familiares sugerem uma base genética para sua epilepsia.